2023
DOI: 10.1007/s10549-023-06871-w
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen therapy after breast cancer diagnosis and breast cancer mortality risk

Abstract: Purpose The safety of local estrogen therapy in patients on adjuvant endocrine treatment is questioned, but evidence on the issue is scarce. This nested case–control registry-based study aimed to investigate whether estrogen therapy affects breast cancer mortality risk in women on adjuvant endocrine treatment. Methods In a cohort of 15,198 women diagnosed with early hormone receptor (HR)-positive breast cancer and adjuvant endocrine treatment, 1262 women d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…A recent Swedish case-control study showed no increase in breast cancer-specific mortality in patients with breast cancer who used estrogen but did not distinguish between vaginal or systemic estrogen. 14 In the absence of trials of vaginal estrogen therapy in breast cancer, the findings of this study provide some reassurance that patients with breast cancer who received vaginal estrogen therapy were not at a markedly higher risk of breast cancer-specific mortality and appear to support national guidelines suggesting that vaginal estrogen therapy can be considered for genitourinary symptoms if nonhormonal treatments are unsuccessful. 3,15 The systemic HRT associations were examined for completeness but should not be a factor in clinical decisions given the wide CIs and previous trial observations of increased risks of recurrence with systemic HRT.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…A recent Swedish case-control study showed no increase in breast cancer-specific mortality in patients with breast cancer who used estrogen but did not distinguish between vaginal or systemic estrogen. 14 In the absence of trials of vaginal estrogen therapy in breast cancer, the findings of this study provide some reassurance that patients with breast cancer who received vaginal estrogen therapy were not at a markedly higher risk of breast cancer-specific mortality and appear to support national guidelines suggesting that vaginal estrogen therapy can be considered for genitourinary symptoms if nonhormonal treatments are unsuccessful. 3,15 The systemic HRT associations were examined for completeness but should not be a factor in clinical decisions given the wide CIs and previous trial observations of increased risks of recurrence with systemic HRT.…”
Section: Discussionsupporting
confidence: 59%
“…Two small cohort studies found no increase in cancer recurrence in patients with breast cancer who received vaginal estrogen therapy, but both studies included fewer than 10 recurrences in the exposed group. A recent Swedish case-control study showed no increase in breast cancer–specific mortality in patients with breast cancer who used estrogen but did not distinguish between vaginal or systemic estrogen …”
Section: Discussionmentioning
confidence: 99%
“…The loss of tumor transcription regulation plays an important role in the biological function of the normal body, while taberrant regulation often leads to the occurrence and development of tumors, and nally it is the estrogen pathway. The estrogen pathway plays a very important role in breast cancer, which has been supported by a large amount of data [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…At the first visit, we reviewed previous treatment records. Regarding the classification of breast cancer treatment, we mimicked previous studies [ 22 ] and created the classification.…”
Section: Methodsmentioning
confidence: 99%